Evaluation of the Effects of Breast Cancer Screening Training Based on the Systematic Comprehensive Health Education and Promotion Model on the Attitudes and Breast Self-examination Skills of Women - Khadije Mirzaii; Shadan Nessari Ashkezari; Talat Khadivzadeh; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2016)
Background: Improvement of attitudes toward breast cancer positively affects the screening behaviors of women. Imagery has been shown to have a positive impact on the screening behaviors of women. Aim: This study aimed to investigate the effects of breast cancer screening training based on the systematic comprehensive health education and promotion (SHEP) model on the attitudes and breast self-examination skills of women. Method: This quasi-experimental study was conducted at two urban healthcare centers of Mashhad, Iran in 2015. Participants were 120 women covered by these health centers, who received training on breast cancer screening based on the SHEP model. Intervention consisted of evaluation (literature review, topic selection), implementation (developing instruments, educator training, training of participants), and assessment (pretest-posttest). Data were collected using researcher-made questionnaires of attitude and breast self-examination (BSE) checklists. Data analysis was performed in SPSS version 20 using independent t-test and Mann-Whitney U test. Results: In the intervention and control groups, 55 (91.7%) and 56 (93.3%) participants were married, respectively. Results of Mann-Whitney U test before intervention showed no significant differences between the groups regarding the mean scores of attitude and breast self-examination skills (P>0.05). After a four-week follow-up, independent t-test revealed a significant difference between the groups in terms of the mean score of attitude (P